Controllable ligand spacing stimulates cellular mechanotransduction and promotes stem cell osteogenic differentiation on soft hydrogels - Zhang, Man; Sun, Qian; Liu, Yiling; Chu, Zhiqin; Yu, Leixiao; Hou, Yong; Kang, Heemin; Wei, Qiang; Zhao, Weifeng; Spatz, Joachim P.; Zhao, Changsheng; Cavalcanti-Adam, Elisabetta A. (Biomaterials, 2021)
Hydrogels with tunable mechanical properties have provided a tremendous opportunity to regulate stem cell differentiation. Hydrogels with osteoid (about 30-40 kPa) or higher stiffness are usually required to induce the osteogenic differentiation of mesenchymal stem cells (MSCs). It is yet difficult to achieve the same differentiation on very soft hydrogels, because of low environmental mechanical stimuli and restricted cellular mechanotransduction. Here, we modulate cellular spatial sensing of integrin-adhesive ligands via quasi-hexagonally arranged nanopatterns to promote cell mechanosensing on hydrogels having low stiffness (about 3 kPa). The increased interligand spacing has been shown to regulate actomyosin force loading to recruit extra integrins on soft hydrogels. It therefore activates mechanotransduction and promotes the osteogenic differentiation of MSCs on soft hydrogels to the level comparable with the one observed on osteoid stiffness. Our work opens up new possibilities for the design of biomaterials and tissue scaffolds for regenerative therapeutics.
Available online 23 November 2020
Gesehen am 17.03.2021